The second laplace-Beltrami operator on rotational hypersurfaces in the euclidean 4-space - Güler, Erhan; Kişi, Ömer; Kişi, Ömer (Yıldız Teknik Üniversitesi, 2017)
We consider rotational hypersurface in the four dimensional Euclidean space. Wecalculate the mean curvature and the Gaussian curvature, and some relations of therotational hypersurface. Moreover, we de ne the second Laplace-Beltrami operator andapply it to the rotational hypersurface.
Keywords: 4-space; Rotational hypersurface; Gaussian curvature; Mean curvature